2010
DOI: 10.1148/rg.301095076
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Abdominal MR Imaging: Approaches to Common Problems

Abstract: Abdominal magnetic resonance (MR) imaging involves many challenges and is complicated by physiologic motion not encountered to the same degree in other regions of the body. Problems that uniquely affect abdominal MR imaging include motion artifact (from respiratory, cardiac, gastrointestinal, and voluntary movement), susceptibility artifact, conductive and dielectric effects, and wraparound artifact. Techniques to minimize these artifacts often need to be addressed within the time constraints of a single breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 31 publications
0
79
1
Order By: Relevance
“…A wide variety of approaches have been developed to deal with motion artifacts at body MR imaging (22). These approaches include synchronization of image acquisition to respiratory motion, changes in the acquisition parameters to minimize the effect of motion on image quality, and accelerated image acquisition (Table).…”
Section: Motion Artifacts Physiologic Motion-related Artifactsmentioning
confidence: 99%
“…A wide variety of approaches have been developed to deal with motion artifacts at body MR imaging (22). These approaches include synchronization of image acquisition to respiratory motion, changes in the acquisition parameters to minimize the effect of motion on image quality, and accelerated image acquisition (Table).…”
Section: Motion Artifacts Physiologic Motion-related Artifactsmentioning
confidence: 99%
“…This result correlated with the SNR equation, which is inversely proportional to the square root of the receiver BW. 22,23 It was reported that decreasing the receiver BWallows an increasing TE 22 and ES. 14 Although there were changes in TE, ES and scanning time, no obvious statistically significant difference was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the artefacts in the PA images were recorded. A mid-transverse section (image number 29, b2 value 5 1000 s mm 22 ) was chosen for measurement. A straight line was drawn through the centre of PA, which arrived at the inner margins of two parallel artefacts in the image.…”
Section: Phantom Studiesmentioning
confidence: 99%
“…Moreover, without ionizing radiation, repeated MR scans can routinely be used for observation of postoperative LN metastasis and therapeutic effects. In contrast, a relatively long scanning time makes MRI more susceptible to motion artifacts from breath or gastrointestinal peristalsis [38]. That may limit its use in evaluating regional LNs of chest and abdominal malignancies.…”
Section: Computed Tomographymentioning
confidence: 99%